Familien mit multipler Elternschaft Entstehungszusammenhänge, Herausforderungen und Potenziale - Bergold, Pia; Buschner, Andrea; Mayer-Lewis, Birgit; Mühling, Tanja (Verlag Barbara Budrich, 2017)
How is family life structured and lived beyond current family models? In the articles on family forms with multiple parenthood, the authors describe the connections and quantitative distribution of adoptive, foster, step and rainbow families as well as families after gamet donation and discuss their challenges and potentials. Subsequently, the current legal framework of these family forms are presented and the need for reform is pointed out. A further contribution deals with the representation of families in television series. Finally, important ethical questions in the context of multiple parenthood are discussed. The book is aimed at specialists in family, child and youth welfare, family sociologists and social scientists from other disciplines. The book is intended to enable them to broaden their view of the family by highlighting important topics that are important in family life with multiple parenthood.